Diarrhea illness in livestock keeping households in Cambodia: An analysis using a One Health framework - Asakura, Shingo; Khieu, Borin; Seng, Sokerya; Pok, Samkol; Ty, Chhay; Phiny, Chiv; Srey, Teng; Blacksell, Stuart D.; Gilbert, Jeffrey; Grace, Delia; Alonso, Silvia (Frontiers in Sustainable Food Systems, 2023)
Background Most of the diarrheal pathogens are zoonotic, and transmission of the pathogens can occur by contaminated food, water, environment and direct contact with animals especially for livestock keepers. Yet little is known of the relative importance of different risk factors especially in under-studied countries. The objectives of this study were to identify risk factors for diarrhea in livestock keepers in Cambodia and to detect bacterial organisms of diarrhea from both human and livestock with the concept of One Health approach. Of special interest were links between food and diarrhea, and between livestock-keeping and diarrhea. Material and methods We used an existing dataset from a questionnaire survey conducted in 400 livestock farms in Prey Veng and Kampot Prefectures between February and March 2013 as well as laboratory results on bacterial isolation from fecal and swab samples from livestock and poultry and up to 3 human stool samples from households reporting diarrhea in the previous 2 weeks, defined as having 3 soft stools within 24 hours. Univariable and multivariable risk factor analyses were performed by generalized linear mixed model. Results Household-level diarrhea incidence rate was 9.0% (36/400). The most statistically significant factor associated with diarrhea in multivariable analysis was drinking and cooking water treatment (OR=0.31, 95%CI: 0.15-0.64, p=0.004), followed by number of days consuming egg within 2 weeks (OR=1.14, 95%CI: 1.03-1.27, p=0.015), keeping poultry (OR=0.39, 95%CI: 0.15-0.99, p=0.047) and family size (OR=1.24, 95%CI: 1.00-1.54, p=0.051). Animal samples for bacterial culture test were collected at 279 cattle, 165 pig and 327 poultry farms, and bacteria were detected from 6 farms. In human samples, 17 out of 67 individual samples were positive for the culture test. No association was found in bacteria detection between animal and human within household-level. Conclusions It has often been hypothesized that keeping livestock may increase incidence of diarrhea through multiple pathways. Contrary to this, we found livestock-keeping was not associated with increased risk, but food-related behaviors were strongly associated with increased risk. We discuss mediating and confounding factors and make recommendations for reducing the burden of diarrheal disease in Cambodia and more widely in low- and middle-income countries.